Implementation of the Duties and Authorities of the Community Health Center in Managing Medical Waste as a Form of Environmental Health Protection (Case Study at the Wonosalam 2 Health Center, Demak) - Jannah, Raudhotul; Nurmardiansyah, Eko; Sulistyanto, Hadi (Universitas Katolik Soegijapranata Semarang, 2023)
Health is one of the human rights, the fulfillment of which is the responsibility of the government in every country, Puskesmas is the agency that organizes government affairs in the health sector in the sub-district. The author chose the Wonosalam 2 Demak Health Center as the object of this research.This study aimed to determine the duties and authorities of the Wonosalam 2 Demak Health Center in managing medical waste as a form of environmental health protection and to determine the extent of the obstacles to the medical waste management process. The research method uses a sociological juridical approach by discussing its juridical aspects as well as discussing social aspects which cover certain legal phenomena with the main data collection method being primary data, namely through observation, interviews, distribution of questionnaires and surveys as well as supporting data is secondary data taken from the study. References. Methods of data analysis using qualitative normative analysis.The obstacle factor that became an obstacle to the management of medical waste at the Wonosalam 2 Demak Health Center was the absence of internal SOP work instructions so the management of medical B3 waste had not been carried out systematically from start to finish. Lack of medical waste management knowledge from health workers or medical personnel as well as competence from environmental sanitation who are not yet certified will become obstacles to proper medical waste management.